Oscillation criteria for second order elliptic equations with damping term - Xu, Zhiting (Utilitas Mathematica, 2007)
Oscillation criteria for the second order nonlinear elliptic differential equation with damping term (Equation Presented) are obtained. The results of this paper extend and improve some known oscillation criteria in the literatures.